Attitudes among Occupy DC participants about the use of violence against police - Maguire, Ed (Policing and society, 2018)
Social movements often embrace nonviolent civil disobedience strategies. At the same time, social movements sometimes attract participants with different temperaments and different views on the morality or utility of using violence against police. Moreover, the use of force or procedurally unjust tactics by police may influence these views, instigating rebellion and support for the use of violence against police by protesters. This paper examines the nature and correlates of attitudes toward using violence against police among Occupy DC participants in Washington, DC. Data are drawn from a survey of 136 Occupy DC participants. We provide descriptive statistics that summarise Occupiers’ attitudes toward the use of violence against police, and test hypotheses about factors that may be associated with these attitudes. Our findings show that a non-trivial subset of participants appears to embrace the use of violence against police, and that these attitudes toward violence are associated with perceptions of the extent to which police treat protesters in a procedurally unjust manner.